Parkon® in the treatment of multiple sclerosis. A pilot study - Goldstein NI; Golubev VL; Goldstein RN (Open Journal of Parkinson's Disease and Treatment - Peertechz Publications, 2020)
Multiple Sclerosis (MS) is one of the most common chronic demyelinating diseases of the central nervous system. The disease affects and relatively quickly leads to disability in mainly people 15-40 years of age. The development of MS can occur progressively or with exacerbations and remissions. The pathogenesis of the disease is based on an autoimmune process directed against myelin or myelin-producing CNS oligodendrocytes. In recent years, in the mechanisms of death of myelin-synthesizing oligodendrocytes, more and more attention has been paid to metabolic shifts. An important role is played by the activation of astro- and microglia, impaired neurotransmitter metabolism and apoptosis